De la inconstitucionalidad de la compra de renuncias obligatorias de las y los servidores públicos. - Chulde Narváez, Marco Vinicio (2017)
The Republic Constitution of Ecuador, in a short time has experimented a serie of contradictions about Juridical Normatiwe infra constitutional to make the juridica! insecurty (ho mean problom to be resoleed with the creation of the juricical figure of voluntary obligatory renuncialions decreed by The Republic President, they form a clear violation of the constitutional duties and guarantoos of the public workers lo apply the Excecutive Duty, since il opposes to the Supreme Law so, il is important to declarate he unconstitudionality. For this reason, the fundament of this investigation radicales in iho problem created by the foros in the article N? 108 of the General Regulation of the Publle Serdico Law, which is originated ihrough Ihe article N* 8 of tho executive decroc. lt establishes the purchase of obligatory renunciations in order to terminate wiih ihé. Contractual relation with the public workers; alihough the Republic President has the faculty to dictate the regulations of all laws and also the oxecutive decree, ll does nol mean that be has the power to oppose the spiril of the Constitution kke a Supreme Nom, nolicing hal even organ with normative faculty has to adequate formality and materially, the juridical normes to he rights prevered in the Constitution and the international treaties, either a regulation can be opposed lo the Organic Law such as he Public Worker Law, then this norm establishes he purchase of renunciationa wlh rormuneration, and its inclusion in the regulation of this Law, Il outcomes pernicious every time that it wolates ho public worker mghts of ihe work and the principles of the stability and the unrenounceability of ibeir rights, because of jundical principle aboul polibes, subordinates to the nght belter han the right subordinates lo the politie. 1 is needed thal he decreer have to understand about his! her attributes lo sanction and to expedite the regulations to the application of the Laws, thoy can mol appose umder any concep lo he constilulional norms by ihe principle al constitutional supremacy, even under the mistaken principle about the general interest is ower the particular interest, which pretends to make appearing, since this circumstance thia principle is not applied to ihe right of the citizens to ihe Ire choosed work, to he guaranty of the stabiliby and the unrencunceaabdlity al the nghts, particularly about publhe workers, it does mol only oppress to a particular imerea! bulihe human nohtuehich can not ha alibiad